Differentiation of deer species of the genus Mazama by track morphometry - Angeli, Thais [UNESP]; Oliveira, Marcio Leite de [UNESP]; Duarte, Jose Mauricio Barbanti [UNESP] (Taylor & Francis Ltd, 2014)
We analyzed morphometric variables of tracks of the five species in the genus Mazama known from Brazil to determine if footprint morphometry can distinguish these species. Tracks from adult M. americana, M. bororo, M. gouazoubira, M. nemorivaga and M. nana maintained at the Deer Research and Conservation Center (NUPECCE) were recorded on a carpet of fine wet sand. Discriminant analysis was successful (99.28%) at classifying the Amazon Rainforest species M. americana and M. nemorivaga whereas for the Atlantic Forest species it was not possible. The analysis of variance (ANOVA) analysis showed longer and wider tracks of M. americana in comparison with other Mazama species, probably due to its larger body size. We do not recommend species identification based on the morphometry of tracks, except for the Amazonian species when imprints have been formed under similar conditions.
Keywords: species identification; morphometry; footprints; deer; Mazama